EC4 European Syllabus for Post-Graduate Training in Clinical Chemistry and Laboratory Medicine: Version 3 - 2005 - Zerah, S.; McMurray, J.; Bousquet, B.; Baum, H.; Beastall, G.H.; Blaton, V.; Cals, M.-J.; Duchassaing, D.; Gaudeau-Toussaint, M.-F.; Harmoinen, A.; Hoffmann, H.; Jansen, R.T.; et al. (Clinical Chemistry and Laboratory Medicine, 2006)
The EC4 Syllabus for Postgraduate Training is the basis for the European Register of Specialists in Clinical Chemistry and Laboratory Medicine. The syllabus: • Indicates the level of requirements in postgraduate training to harmonise the postgraduate education in the European Union (EU); • Indicates the level of content of national training programmes to obtain adequate knowledge and experience; • Is approved by all EU societies for clinical chemistry and laboratory medicine. The syllabus is not primarily meant to be a training guide, but on the basis of the overview given (common minimal programme), national societies should formulate programmes that indicate where knowledge and experience is needed. The main points of this programme are: • Knowledge in biochemistry, haematology, immunology, etc.; • Pre-analytical conditions; • Evaluation of results; • Interpretations (post-analytical phase); • Laboratory management; and • Quality insurance management. The aim of this version of the syllabus is to be in accordance with the Directive of Professional Qualifications published on 30 September 2005. To prepare the common platforms planned in this directive, the disciplines are divided into four categories: • General chemistry, encompassing biochemistry, endocrinology, chemical (humoral), immunology, toxicology, and therapeutic drug monitoring; • Haematology, covering cells, transfusion serology, coagulation, and cellular immunology; • Microbiology, involving bacteriology, virology, parasitology, and mycology; • Genetics and IVF. © 2006 by Walter de Gruyter.
Keywords: Clinical Chemistry and Laboratory Medicine; Postgraduate education; Professional qualifications; Quality